EhVps35, a retromer component, is involved in the recycling of the EhADH and Gal/GalNac virulent proteins of Entamoeba histolytica - Díaz-Valdez, Joselin; Javier-Reyna, Rosario; Montaño, Sarita; Talamás-Lara, Daniel; Orozco, Esther (Frontiers in Parasitology, 2024)
The retromer is a highly conserved eukaryotic complex formed by CSC and SNX-dimer subcomplexes, whose function is protein recycling and recovery from the endosomes to conduct the target molecules to the trans-Golgi network or the plasma membrane. The protozoan responsible for human amoebiasis, Entamoeba histolytica, exhibits an active membrane movement and voracious phagocytosis, events in which the retromer may be fully involved. EhVps35 is the central member of the CSC retromeric subcomplex, because it binds EhVps26 and EhVps29, the other two CSC members, allowing the position of the retromer at the membranes. In this work, we studied the EhVps35 structure and its role in the recycling of virulence proteins, particularly those involved in phagocytosis. Our results revealed EhVps35 located at the plasmatic and endosomal membranes, and in the phagocytic cups and channels. In addition, it follows the target cell from the moment that it contacts the trophozoites. Molecular docking analyses, immunoprecipitation assays, and microscopy studies evidenced that EhVps35 interacts with EhADH, Gal/GalNac lectin, and actin proteins. In addition, experimental evidence showed that it recycles surface proteins, remarkedly, EhADH and Gal/GalNac proteins, two molecules highly involved in virulence. Knock-down of the Ehvps35 gene provoked decrease in protein recycling, as well as impairment of adhesion efficiency and rate of phagocytosis. Actin cytoskeleton was deeply affected by the knock down of the Ehvps35 gene. In summary, our results revealed the participation of EhVps35 in protein recycling and phagocytosis. Furthermore, all together, our results evidenced the concert of finely regulated molecules, including EhVps35, EhADH, Gal/GalNac lectin and actin in the phagocytosis of E. histolytica.